Literatur Review: Pengaruh Terapi Rendaman Air Jahe Hangat terhadap Penurunan Derajat Edema Kaki Ibu Hamil: Literature Review: Effect of Warm Ginger Immersion Therapy on Decreasing Degree of Foot Edema in Pregnant Women - Mardiyah Mardiyah; Nita Hestiyana; Bagus Rahmat Santoso (Jurnal Surya Medika (JSM), 2022)
Introduction: Physiological leg edema can cause discomfort, a feeling of heaviness, and cramps at night. Pathological edema can show signs of danger in pregnancy if edema in the face or in the fingers, severe headaches, and blurred vision resulting from pre-eclampsia. The degree of edema can be reduced by improving blood circulation by soaking the feet in combination with ginger. Aims: To conduct a journal review by identifying the effect of warm ginger water immersion therapy on reducing the degree of leg edema of pregnant women from various literature studies. Methods: The research method was a literature review using several selected sources based on the criteria set by the researcher. Results: From 21 types of literature, it was found that soaking feet using warm ginger water can reduce leg edema in third-trimester pregnant women. Reducing the degree of leg edema by utilizing the content of essential oils and oleoresin (gingerol) compounds which provide a warm feeling and a spicy aroma. Conclusions: Based on the analysis that has been done, it was concluded that the application of warm ginger water immersion therapy to reduce the degree of leg edema in pregnant women has an effect on reducing leg edema in pregnant women, and it was recommended to apply foot soaking therapy as a cheaper and easier non-pharmacological alternative, can also avoid complications from pharmacological therapy (diuretic).